EFEKTIVITAS PENGGUNAAN APLIKASI BANDLAB DALAM MENINGKATKAN KREATIVITAS GURU MUSIK DI SMAN 1 KABUPATEN TANGERANG - Kingkin Prasetyo Wati; Agus Cahyono; Muh Fakhrihun Naam (STKIP Subang, 2025)
Music learning at SMAN 1 Kabupaten Tangerang has long been constrained by the limited availability of musical instruments, requiring teachers to adopt digital technology to sustain instructional quality. This study aims to analyze the effectiveness of the BandLab application in enhancing music teachers’ creativity and its contributions to overall learning quality. Using a qualitative approach with a case study design, data were collected through classroom observations, in-depth interviews, and documentation involving the music teacher and tenth-grade students. The findings reveal that BandLab effectively addresses the scarcity of physical instruments through its virtual instruments, multi-track recording, and collaboration workspace features. The use of this application enhances teachers’ ability to design creative instruction, diversify teaching strategies, and produce innovative digital learning materials. BandLab integration also improves student participation, motivation, and musical competence through digital exploration of rhythm, melody, and harmony. Thus, BandLab is proven effective in enhancing teacher creativity and the quality of music learning in the context of secondary education.